Taxonomic review of the slender mouse opossums of the “Parvidens” group from Brazil (Didelphimorphia: Didelphidae: Marmosops), with description of a new species - Ferreira, Claudilívia; de Oliveira, Ana Cristina Mendes; Lima-Silva, Luan Gabriel; Rossi, Rogério Vieira (Zootaxa, 2020)
The genus Marmosops comprises small marsupials of the family Didelphidae (≤ 200 g), widely distributed in a variety of lowland rainforest and montane forest habitats, extending from Panama to southern Bolivia and southeastern Brazil. The smallest species of the genus are included in the “Parvidens” group, which includes M. pakaraimae, M. parvidens and M. pinheiroi. Although the monophyly of this group and species relationships are well defined, molecular studies have indicated that M. pinheiroi may represent a species complex, which has never been tested based on morphological analysis. In this study, we present the taxonomic review of M. pinheiroi based on the largest sample ever analyzed of this species. The external and craniodental morphology of 613 specimens of M. parvidens and M. pinheiroi from the northern, eastern, central and southern Brazilian Amazonia and northern Cerrado were examined. Besides, 28 craniodental dimensions were measured from adult specimens to support univariate and multivariate statistical analyses. Our results corroborate the validity of M. parvidens and indicate that M. pinheiroi is a complex formed by three species – M. pinheiroi (s. s.), distributed to the north of the Amazon River, from eastern Venezuela to the state of Amapá in Brazil; M. woodalli, which occurs east of the Xingu river and in the Marajó Island, state of Pará, extending to the east in the states of Tocantins and Maranhão; and a new species that occurs from the left bank of the Madeira River to the left bank of the Xingu River, herein described. Although the great morphometric similarity, species of the M. pinheiroi complex tended to be more different from each other than to M. parvidens in both univariate and multivariate analyses. Morphologically, these species may be positively distinguished by unique combinations of characters, such as dorsal and ventral fur coloration, arrangement of gray based hairs on the venter, supraoccipital shape, development of anterior and posterior portions of the M3 stylar shelf, continuity or not between the preprotocrista and anterior labial cingulum along the anterior margin of the upper molars, development of the metaconule in the upper molars, and number of cusps of the m4 talonid. The present work provides new perspectives for studies based on molecular data in order to test the species hypotheses recognized here and evaluate to what extent the Tapajós, Madeira, and Araguaia-Tocantins rivers actually isolate Marmosops populations.